Masculine Identity and Identification as Ethnomethodological Phenomena: Revisiting Cameron and Kulick - Benwell, Bethan (Gender and Language, 2011)
The aim of this paper is to explore possible discourse and conversation analytical approaches to articulations of masculinity in and around sites of popular culture. The research presented in this paper arises from work on the relationship between men’s magazines, constructions/discourses of masculinity and lived cultures of masculinity. My particular interest in this paper is to explore the process by which we assign gendered identities to familiar cultural discourses, and in doing so, to engage critically with the ideas of Cameron and Kulick (2003; 2005) who have postulated a distinction between ‘identity’ and ‘identification’ as a means of reconceiving the relationship between discourse and sexuality. By adopting an ethnomethodological approach to conversational data, I will argue that it is possible to demonstrate how gendered identities - both the explicit alignments and claim-staking of ‘identity’ work, as well as the more ambivalent, shifting and contradictory footings that could be thought to characterise ‘identification’ - are available for analysis on the surface of talk. In a final analysis, I move beyond strict ethnomethodological principles in order to extend this consideration of ‘identity’ and ‘identification’ to a particular popular discourse - that of ‘gross out’ - whose intuitive labelling as masculine can be traced and supported by the forms and contexts of the various intertexts within which it occurs.